Learning preferences of third year KOD dental students: teaching routine prosthodontic procedures using two different methods - Mohamed Rosni, Fakhrul Zaman; Asror, Muhammad Afif; Wan Nik, Wan Noor Nazayan; Zainol, Iswan Zuraidi; Che Musa, Muhd Firdaus; Abela, Stefan (2020)
Introduction: Video-based teaching (VBT) method was introduced in prosthodontics to supplement the conventional method of power point lecture (PPL) to effectively deliver preclinical knowledge prior to hands-on-simulation. Aim: To identify learning effectiveness and preferences between the PPL and VBT methods in a fixed prosthodontics classes amongst first-year clinical dental students (Year-3) at International Islamic University of Malaysia (IIUM). Method: A cross-over study design comprising teaching sessions (PPL and VBT methods), test assessment and questionnaire on onlay-subjects were conducted amongst third-year dental students (n=57) at IIUM in 2019. They were divided into 2 groups; exposed by different method of teaching; followed by other method. They were tested twice for teaching effectiveness in each session and survey preference post-combined methods. Data were analysed using SPSS v25, includes pre and post-tests. Results: All 57 students participated. The test score for group A (first-exposed to VBT) is significantly higher than students in group B (first-exposed to PPL) [p=0.034]. Nevertheless, each group shows an improvement in their score and were significantly different post-implementation of both methods (Group A [p=0.002]; Group B [p=0.003]). Combination methods of VBT-PPL (43.9%) was perceived as greatest preference. More female significantly perceived VBT content is just right (p=0.010) and could not completely replaced the PPL and be the only method (p=0.031) than male. Conclusion: Third-year IIUM dental students demonstrated that VBT is required to complement and combined with the PPL to provide a better understanding of prosthodontics subject; specifically, for the onlay-topic. There were variations in students’ preference by gender.